Dating Violence Experiences among Youths with Same-gender and Multi-gender Dating Partners: A Dyadic Concordance Type Approach - Blais, Martin (Journal of interpersonal violence, 2022)
Dating violence (DV) among youth is widespread and is now established as a significant public health problem. Yet, few studies have assessed DV experiences among youth with same-gender or multi-gender dating partners, and most failed to consider bidirectional DV. We analyzed self-reported dyadic concordance types (DCTs) among 295 youths (52% girls) who dated same-gender and multi-gender partners in the last 12 months using an adapted version of the Conflict in Adolescent Dating Relationships Inventory. Youths were classified in one of three DCTs: self-only (unidirectional perpetration of DV by the participant), partner-only (unidirectional victimization perpetrated by their partner) or both (bidirectional DV, where partners are both perpetrators and victims of DV). Overall prevalence rates of DV among sexual minority youths (SMYs) range from 11.5% for threats, to 51.2% for psychological violence, with physical and sexual violence reported by about one-fourth of participants. The both DCT was the most common pattern for psychological (59.6%) and physical (50.6%) DV across gender, while most threatening behaviors were reported as perpetrated by the partner only (47.1%). Girls were more likely to report sexual DV as partner-only perpetrated (63.6%), whereas boys reported higher rates of both (44.2%) and self-only (34.9%) perpetrated sexual violence. Because healthy intimate relationships can play a supportive and positive role in transitioning toward adulthood, it is crucial that DV prevention becomes more inclusive of sexual and gender diversity.